Penilaian Kondisi Jalan Menggunakan Metode International Roughness Index (IRI) Dan Surface Distress Index (SDI) Pada Ruas Jalan Akses Terminal Alang-Alang Lebar (Studi Kasus: Sp. Soekarno Hatta – Bts. Kota Palembang Km 13) - Sartika Nisumanti; Dimas Prawinata Prawinata (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Road infrastructure is needed to support economic growth in line with regional accessibility and mobility in economic growth support. The road link of Sp. Soekarno Hatta- Palembang border is a national road connectivity that link South Sumatra Province with other provinces. Volume and overload Traffic will affect road pavement conditions, therefore it is necessary need maintenance so that road remain in steady condition. Right-on-target road handling requires prior planning based on accurate pavement condition survey data. One of way to determine the condition of the pavement is obtained by using a roughness measuring instrument. This tool is used to determine uniformity in obtaining the flatness value of the road surface which is expressed in the International Roughness Index (IRI) value. In addition, the evaluation of pavement conditions can be carried out using the Surface Distress Index (SDI) method. This research examines the condition of the pavement on the road Sp. Soekarno Hatta-. Palembang border, by comparing the values of IRI and SDI in order to obtain a road management proposal which is useful as input for road administrators in road maintenance.The results showed that the IRI method obtained a condition value of 67%, a minor damage condition was 33%. Meanwhile, the SDI method obtained a moderate value of 66% and 34% lightly damaged conditions. The results of the two methods show a slight difference in the proportion of the value of the pavement condition by 1%. The results of road condition services using the IRI and SDI methods can provide an illustration that from the total length of the observed road at km 9 + 000 - 12 + 000, belong the medium category that requires routine maintenance, beside that, km 12 + 000 - 13 + 000 the road belong a light damaged that periodic maintenance is needed..Keywords: IRI, SDI, Pavement performance